TRANSITION SHOCK EXPERIENCED BY NEW NURSES: AN EXAMPLE FROM TURKEY - Dertli, Semiha; Çevik Aktura, Seher (Inonu University, 2024)
This research was carried out to determine the transition shock to the profession in nurses. This descriptive study was conducted with 221 nurses who started to work in university hospitals in eastern Turkey between March and April 2022. Data were collected using the Introductory Information Form, and the Nursing Transition Shock Scale (NTSS). The mean score of the (NTSS) in Nursing was found to be 2.65±0.75 (moderate). The multiple linear regression model demonstrated that there was a statistically significant relationship between choosing the nursing department willingly, having an internship, receiving in-service training at the start of the profession, being self-confident in applying the knowledge and skills required by the nursing profession, having the communication skills required by the nursing profession and experiencing stress in transition from student role to profession and NTSS mean scores, and showed that these variables explained 20.7% of the total variance. In the study, it was found that the transition shock scores of the nurses were moderate. The research provides a perspective to nursing educators and managers in terms of showing the transition shock experienced by nurses who have just started to work and the factors affecting it. © 2024, Inonu University. All rights reserved.
Yeni Hemşirelerin Yaşadığı Geçiş Şoku: Türkiye’den Bir Örnek
Keywords: Nursing; Occupational competence; Occupational role; Transition shock